1988
DOI: 10.1002/j.1460-2075.1988.tb03297.x
|View full text |Cite
|
Sign up to set email alerts
|

Binding site requirements for pea nuclear protein factor GT-1 correlate with sequences required for light-dependent transcriptional activation of the rbcS-3A gene.

Abstract: Nuclear protein factor GT‐1 binds to sequence boxes II, III, II* and III* upstream of the light‐responsive pea rbcS‐3A gene. We have shown previously that box II and box III are required for expression of rbcS‐3A when redundant elements upstream of −170 (relative to the transcription start site) are removed. Here we present evidence that deletion and substitution mutations downstream of −170 which eliminate expression also decrease binding. Using a series of 2 bp substitution mutations we have defined a core o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
197
1
1

Year Published

1989
1989
1997
1997

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 227 publications
(207 citation statements)
references
References 39 publications
(25 reference statements)
8
197
1
1
Order By: Relevance
“…rbcS-CMAs 1, 2, 3, and 6; cab-CMAs 1 and 4; and the CMAs found in gapA, gapB, ppdk, atpC-D, pal, and 4-cl genes. GT-1 elements (core motif, GGTTAA; Green et al, 1988) are invariant components of only a few CMAs from dicotyledonous PhANGs such as rbcS-CMAs 2 and 3 and LsCMA1. Modules that are similar in sequence to the rbcS box I1 (GTGTGGTTAATATG), the prototype of GT-1 e l e m e n t s ( G r e e n et al, 1987), are also found in cab-CMA3, rbcS-CMA6, Pc-CMA2, rbcA-CMAl, and gapBCMAl (Fig.…”
Section: Comparative Analysis Of Lre-associated Cmasmentioning
confidence: 99%
“…rbcS-CMAs 1, 2, 3, and 6; cab-CMAs 1 and 4; and the CMAs found in gapA, gapB, ppdk, atpC-D, pal, and 4-cl genes. GT-1 elements (core motif, GGTTAA; Green et al, 1988) are invariant components of only a few CMAs from dicotyledonous PhANGs such as rbcS-CMAs 2 and 3 and LsCMA1. Modules that are similar in sequence to the rbcS box I1 (GTGTGGTTAATATG), the prototype of GT-1 e l e m e n t s ( G r e e n et al, 1987), are also found in cab-CMA3, rbcS-CMA6, Pc-CMA2, rbcA-CMAl, and gapBCMAl (Fig.…”
Section: Comparative Analysis Of Lre-associated Cmasmentioning
confidence: 99%
“…To investigate whether the Gill protected region was related to the GT-1 motif, we used dimers of the wild-type or mutant GT-1 binding site corresponding to box II (GGTTAA) of the pea RBCS-3A promoter (Green et al, 1988;Kuhlemeier et al,1988) as DNA competitors in gel shift assays. When an excess of unlabeled DNA containing the wild-type box II dimer sequence was included in the binding assays, all shifted bands were eliminated by competition ( Figure 4A, competitor GT-1w).…”
Section: The Clll Region Of the Rpl27 Promoter 1s Related To The Lighmentioning
confidence: 99%
“…The pea RBCS-3A promoter has previously been extensively studied, and box II** has been shown by DNase I footprinting and gel retardation studies to bind the plant nuclear factor GT-1 (Green et al, 1988). However, the S2 site had not been identified in box I)** (Green et al, 1988;Gilmartin et al, 1990). To ascertain that S2F indeed binds to pea RBCS-3A box II**, we performed the following competition experiment.…”
Section: The S2 Site 1s Conserved In the Promoter Of Nuclear Genes Enmentioning
confidence: 99%
See 1 more Smart Citation
“…GT-1 boxes, found to be located upstream of genes encoding the small subunit of ribulose-1,5-biphosphate carboxylase, have been implicated in mediating the light-inducible expression of these genes (9,15). A six-residue core sequence, GGTTAA, within one of the GT-1 boxes has been identified as essential for the binding of GT-1 transcription factor in vitro (10). In this study, we demonstrate that expression of shsp-1 is regulated by light as well as by heat (Fig.…”
Section: Identification Of the Transcription Initiationmentioning
confidence: 99%